Protection of Workers’ Rights: A Legal Review of PT X - Salwa Rabiah; Satino (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
This study examines the implementation of Government Regulation No. 6 of 2025 concerning the Amendment to Government Regulation No. 37 of 2021 on the Administration of the Job Loss Insurance Program (JKP), focusing on a case study of unilateral termination at PT X. The research is motivated by the increasing number of unlawful dismissals and the suboptimal enforcement of workers’ legal protection. The study employs an empirical juridical method, collecting data through interviews with the Department of Manpower and Transmigration of DKI Jakarta and qualitative analysis of relevant legislation. Findings reveal that although Government Regulation No. 6 of 2025 enhances worker protection by improving financial benefits, extending claim periods, and reducing employer contributions, its implementation remains hindered by low legal compliance and limited socialization among companies. The PT X case exemplifies violations of the termination procedures stipulated in the Manpower Law and Government Regulation No. 6 of 2025. This regulation reflects a proportional distribution of responsibility between the state, employers, and employees. This research emphasizes the need for stronger law enforcement and continuous evaluation to ensure that the regulation’s primary goals, worker welfare and business sustainability are effectively achieved.